Effect of a muscular resistance training program to improve physical fitness components in older females - José Antonio Gonzalezjurado; Juan Antonio León-Prados; Alberto Nuviala Nuviala; Edgardo Cristian Molina Sotomayor (Pensar en Movimiento)
The aim of this study was to estimate the effect of resistance training program in the fitness of untrained older women. Fourteen women in Chile (65,86 ± 6.55 kg, 1.55 ± 0.06 m, 67.71 ± 5.31 years old) underwent a program of strength training for 6 weeks, performing Back Test (BT) , Leg Press (PS), Bench Press (BP) and Knee Extension (ER) at 3 sessions per week, recording measurements before and after the period of training on maximal dynamic strength (FDM) estimated indirectly by the mass displaced in a maximal repetitions test on those exercises and maximal oxygen consumption (VO2máx) estimated by the UKK test. The results show significant differences between the pre-and post-test values (mean ± SD) of estimated VO2max (11.02 ± 7.26 and 15.57 ± 5.17 ml kg-1 min-1, P <0.05) and FDM estimated the pre-and post-tests (mean ± SD) in LS: 43.09 ± 6.19 and 51.27 ± 9.07 N (p <0.01), PB: 21,12 ± 5.77 and 29.08 ± 7.47 kg (p <0.001), ER: 18.60 ± 5.07 and 21.99 ± 5.21 kg (p <0.05) and PS: 18,60 ± 5.07 and 21.99 ± 5.21 kg (p <0.05). We conclude that the proposed training program improves the FDM in this sample of older adults.